Numerical and experimental study of the ducted diffuser effect on improving the aerodynamic performance of a micro horizontal axis wind turbine. (15th April 2022) - Rahmatian, Mohammad Ali; Hashemi Tari, Pooyan; Mojaddam, Mohammad; Majidi, Sahand
Abstract: In the present study, the impact of utilizing an encompassing duct on the aerodynamic performance of a micro horizontal axis wind turbine (HAWT) was numerically and experimentally studied. A duct comprised of a diffuser and a flange was designed and constructed. A wind simulator facility and a micro scale wind turbine were employed to conduct the experimental investigations. Measurements of velocity and power output of the turbine have been carried out. The numerical results obtained at different stages of the research were validated separately and then compared with our experimental data and those obtained by other researchers. Consequently, the numerical predictions match well with the experimental measurements. In the first part of the study, fluid flow through the empty duct was analyzed. Then, by adding a nozzle at the diffuser entrance of the original duct, an improved design was proposed and numerically modeled to achieve higher wind speed at the throat position of the duct. The modified design was further enhanced by altering the converging and diverging section's angles (ranging from 0 to 90° with the angle increment step of 5°). Fifty-two different duct configurations have been considered to achieve the optimal angles of the nozzle, the diffuser, and the flange. Moreover, the aerodynamic performance of the micro HAWT was studied in three different conditions: without a duct, with the original duct, and with the improved duct. The results show that the improved duct increases the inlet wind speed from 5 m/s to 10.7 m/s (i.e., up to 2.14 times) at the throat position, which increases the wind speed up to 47% compared to the original duct. Furthermore, the power coefficient of the turbine increases from 0.33 to 1.2 (i.e., up to 3.64 times) in comparison to the case without duct, which increases by about 164% compared to the original duct. Also, employing the improved duct design causes a lower level of flow turbulence kinetic energy compared to the original duct design. This valuable outcome reduces the noise level generated by the system and the dynamics forced exerted by the rotor to other possible downstream structures. Highlights: Three-dimensional numerical simulation of the flow around and within a nozzle-diffuser-flange duct with a wind turbine. Experimental measurement of the aerodynamic performance of a micro HAWT mounted in the duct. Improving the geometry of the duct to increase local wind speed and wind turbine power coefficient. Achieving up to 3.64 time of power coefficient of the wind system using the improved duct.